Fungsi Pemerintah Desa dalam Pembinaan Lembaga Kemasyarakatan - Laode Mustafa R (Laboratorium Jurusan Antropologi, Fakultas Ilmu Budaya, Universitas Halu Oleo, 2014)
The aim of this study was to describe the function of Village Government in the development of Social Institutions in Wawesa Village, District Batalaiworu, Muna. The population of the study was 68 people and set a sample of 50% of the data population. The data collection conducted by distributing questionnaires, interviews, and observations. The results showed that the functions performed by the village government to the development of civil society in the village Wawesa consists of: 1) Increased motivation in the form of suggestion and instruction. This function has been performed for all the community organizations in the village; 2) Provision of facilities, including financial support to the activities of this new institution kemasyarakatan. The function conducted to the form of PKK and Taklim Assembly, while not yet to the LPM and Youth community; 3) Supervision and monitoring to the community-based activities. The institutions have done to all the institutions but with a different emphasis from one institution to another; 4) Upgrading to the board of village government. The upgrading were already done to the board of PKK but not for LPM and Taklim. There were still lack of upgrading function from village government to the community organization and the upgrading were found differ between agencies and with each other. Keywords: village government, community organizations